EFEKTIVITAS MEDIA LAGU CORAK BATIK UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA DALAM PEMBELAJARAN SENI RUPA SEKOLAH DASAR - Hariyastuti, Anik; Andaryani, Eka Titi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problems found at SD Negeri Bedug 01 show that teachers tend to teach only using storytelling and lecture methods in learning Fine Arts. The purpose of this study was to determine the effectiveness of using song media in learning fine arts. The research method used was quantitative using a quasi experimental design. The research design applied was non-equivalent control group design with an experimental class of 20 students and a control class of 20 students as a comparison. The results showed that the application of song media was carried out using Project Based Learning syntax, in the implementation process students tended to be more active, interactive and enthusiastic. The increase in students' cognitive learning outcomes was measured using the N-gain score, the results of the N-Gain test on the pretest and posttest scores obtained an average difference of 0.739 with moderate criteria and a level of effectiveness of 73.95 on a very effective interpretation. While the control class obtained a score of 0.425 with moderate criteria and an effectiveness level of 42.35 on the interpretation of less effective. The description of the data shows that the class that applied the song media obtained an increase in learning outcomes with very effective criteria.